Śrīmallokācāryapraṇīta Mumukṣuppaḍirahasyagranthe Caramaślokaprakaraṇam: Mandrārthadīpikāsahitaśrīmadvaravaramunīndraprasāditavyākhyāsahitam - Piḷḷai Lōkācāryar, 1264-1327
Treatise, with two commentaries, on the liturgy of the Sri Vaishnava sect in Hinduism.